(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hemochromatosis is one of the most common inherited diseases. The prevalence of HFE gene mutations is approximately 1 in 8, and among carriers of the C282Y gene mutation — about 1 in 200. Overall, according to various studies, around 1 million people worldwide suffer from the clinical form of the disease, and approximately 4-5 million are carriers of predisposition to develop hemochromatosis [1]. The prevalence varies significantly across regions: in Northern Europe, the United Kingdom, Ireland, Scandinavian countries, Italy, and France, the carrier frequency of HFE mutations is particularly high. At the same time, in Asian, African, and South American countries, the disease is much rarer, which is associated with a lower frequency of mutations causing hemochromatosis [2].